Histological features of localized scleroderma 'en coup de sabre': a study of 16 cases. (10th October 2013) - Taniguchi, T.; Asano, Y.; Tamaki, Z.; Akamata, K.; Aozasa, N.; Noda, S.; Takahashi, T.; Ichimura, Y.; Toyama, T.; Sugita, M.; Sumida, H.; Kuwano, Y.; et al.
Abstract Background Early lesions of localized scleroderma are histologically characterized by perivascular lymphocytic infiltrate in the reticular dermis and swollen endothelial cells. However, there have been few information regarding histological features other than these findings in localized scleroderma. Objective Since en coup de sabre (ECDS) is a certain subset of localized scleroderma with a relatively uniform clinical manifestation, we focused on this disease subset and evaluated its histopathological features. Methods A total of 16 patients with ECDS were retrospectively evaluated on the basis of clinical and histological findings. Results Regardless of clinical manifestations, vacuolar degeneration was found in all of the ECDS patients. Importantly, keratinocyte necroses were restricted to early and active ECDS lesions. In early ECDS patients (disease duration of <3 years), moderate to severe perivascular and/or periappendageal lymphocytic infiltrate and vacuolar changes in follicular epithelium were more prominent, whereas epidermal atrophy was less frequently observed, than in late ECDS patients (disease duration of ≥6 years). Conclusion Vacuolar degeneration at the dermoepidermal junction is a common histological feature in ECDS and perivascular and/or periappendageal lymphocytic infiltrate and vacuolar degeneration of follicular epithelium are characteristic especially in early ECDS, further supporting a canonical idea that the elimination of mutated epidermal cells by immune surveillance contributes to tissue damage and resultant fibrosis in localized scleroderma.